The movement for reproductive justice: Empowering women of color through social activism - Zavella, Patrica (NYU Press, 2020)
Shows how reproductive justice organizations' collaborative work across racial lines provides a compelling model for other groups to successfully influence change Patricia Zavella experienced firsthand the trials and judgments imposed on a working professional mother of color: her own commitment to academia was questioned during her pregnancy, as she was shamed for having children "too young." And when she finally achieved her professorship, she felt out of place as one of the few female faculty members with children. These experiences sparked Zavella's interest in the movement for reproductive justice. In this book, she draws on five years of ethnographic research to explore collaborations among women of color engaged in reproductive justice activism. While there are numerous organizations focused on reproductive justice, most are racially specific, such as the National Asian Pacific American Women's Forum and Black Women for Wellness. Yet Zavella reveals that many of these organizations have built coalitions among themselves, sharing resources and supporting each other through different campaigns and struggles. While the coalitions are often regional-or even national-the organizations themselves remain racially or ethnically specific, presenting unique challenges and opportunities for the women involved. Zavella argues that these organizations provide a compelling model for negotiating across differences within constituencies. In the context of the war on women's reproductive rights and its disproportionate effect on women of color, and increased legal violence toward immigrants, The Movement for Reproductive Justice demonstrates that a truly intersectional movement built on grassroots organizing, culture shift work, and policy advocating can offer visions of strength, resiliency, and dignity for all.
Keywords: 2000 à aujourd'hui; 2010-2019; LGBTQIA2+; afro-féminisme; amériques; anthropologie; approches et analyses; discipline; droits des femmes*; ethnographie; femmes* immigrantes; identités LGBTQIA2+; intersectionnalité; justice reproductive; justice sociale; militance; périodes historiques; ressource en ligne; régions géographiques; santé; sciences humaines; sociologie; thématiques; violences; violences d'état; violences gynécologiques et obstétricales; états-unis

Living a feminist life - Ahmed, Sara (Duke University Press, 2017)
In Living a Feminist Life Sara Ahmed shows how feminist theory is generated from everyday life and the ordinary experiences of being a feminist at home and at work. Building on legacies of feminist of color scholarship in particular, Ahmed offers a poetic and personal meditation on how feminists become estranged from worlds they critique-often by naming and calling attention to problems-and how feminists learn about worlds from their efforts to transform them. Ahmed also provides her most sustained commentary on the figure of the feminist killjoy introduced in her earlier work while showing how feminists create inventive solutions-such as forming support systems-to survive the shattering experiences of facing the walls of racism and sexism. The killjoy survival kit and killjoy manifesto, with which the book concludes, supply practical tools for how to live a feminist life, thereby strengthening the ties between the inventive creation of feminist theory and living a life that sustains it. https://www.saranahmed.com/
Keywords: 2000 à aujourd'hui; 2010-2019; afrique; afro-féminisme; approches et analyses; care; corps; cours; discipline; fem1000; féminismes noirs; incontournable; intersectionnalité; manifeste; militance; occident; orient; philosophie; premier cycle; périodes historiques; racisme; ressource en ligne; régions géographiques; sciences humaines; sexisme; systèmes d'oppressions; thématiques; violences; émotions; études culturelles